Cylindrical 21700 high-capacity fast-charging lithium battery and preparation process thereof

By using a high-nickel positive electrode and a silicon-doped graphite negative electrode in the cylindrical 21700 high-capacity lithium battery, combined with a single-layer coating separator design, the problem of difficulty in balancing high capacity and fast charging performance of the battery is solved, and high efficiency is achieved. fast charging capabilities and high capacity features while maintaining cost-effectiveness.

CN119361793APending Publication Date: 2025-01-24ZHENGZHOU BAK BATTERY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411790485.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing cylindrical 21700 high-capacity lithium battery is difficult to improve its fast charging performance while maintaining high capacity, and only supports a charging rate of 0.5C at room temperature.

Method used

Using high -nickel positive poles and silicon -doped graphite negative electrodes, combined with single -layer coating diaphragm design, the coating faces the negative electrode, the base film surface is facing the positive electrode, reducing interface impedance, accelerating the migration of lithium ions, and optimized face density and compact design. Improve the high -volume performance of the cell.

Benefits of technology

While significantly improving the fast charging capacity of the battery cell, it ensures the full use of the high capacity characteristics without increasing additional material costs, achieving dual optimization of economic benefits and technical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361793A_ABST
    Figure CN119361793A_ABST
Patent Text Reader

Abstract

The invention discloses a cylindrical 21700 high-capacity fast-charging lithium battery and a preparation process thereof. The lithium battery comprises a positive plate, a negative plate, an electrolyte and a diaphragm, the positive plate comprises a positive current collector and positive slurry coated on the positive current collector; the positive slurry comprises a high-nickel MCN active substance doped with special elements and coated with oxide on the surface, a conductive agent and polyvinylidene fluoride; the negative plate comprises a negative current collector and negative slurry coated on the negative current collector; the negative slurry comprises a silicon material doped graphite active substance, a conductive agent, sodium carboxymethyl cellulose and butadiene styrene rubber; the diaphragm is a single-sided coating diaphragm taking polypropylene or polyethylene as a substrate, the surface of the substrate faces the positive plate, and the surface of the coating faces the negative plate. A high-nickel positive electrode and a silicon-doped graphite negative electrode are adopted, a single-layer coating diaphragm is selected, a coating surface faces the negative electrode, and a base membrane faces the positive electrode, so that the interface impedance is reduced, the lithium ion migration is accelerated, and the capacity performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and specifically to a cylindrical 21700 high-capacity fast-charging lithium battery and a preparation process thereof. Background Art

[0002] With the continuous progress of the times, human beings have increasing performance requirements for new energy batteries, among which the long battery life and fast charging capabilities of lithium-ion batteries have become the focus of attention. For lithium-ion batteries, how to further improve their fast charging performance while maintaining high capacity has become an important issue that needs to be solved urgently. At present, small cylindrical cells such as the 21700 model, with its unique circular structure, can effectively control the expansion of the core during the charging and discharging process. Therefore, it is more suitable to use materials with greater expansion but higher energy density, such as a combination of high-nickel positive electrodes and silicon-based negative electrodes to achieve an energy density of more than 270Wh / kg. However, high capacity and fast charging performance are often difficult to achieve at the same time. High-capacity designs are often accompanied by compromises in fast charging performance, and usually can only support a charging rate of 0.5C at room temperature.

[0003] At present, the industry is mainly working on improving fast charging capabilities from the following four aspects: One is to increase the electrolyte's conductivity by increasing the lithium salt concentration or adding high-conductivity functional additives, so that lithium ions can more smoothly pass through the medium to the negative electrode during charging, achieving fast charging. However, the main disadvantage of this method is the increase in cost; The second is to use a more permeable diaphragm to facilitate lithium ions to pass through the medium to the negative electrode more smoothly during the charging process, thereby improving the fast charging performance. However, this method may lead to problems such as decreased permeability and weakened strength of the diaphragm, posing a potential threat to battery safety; The third is to replace the negative electrode material with better lithium embedding isotropy or perform carbonization coating treatment to accelerate the speed of lithium ions passing through the negative electrode surface and the migration rate inside, thereby improving the fast charging capability. However, negative electrode materials with better isotropy often have lower capacity density, which is not conducive to achieving high capacity goals, and carbonization coating treatment will also increase costs; The fourth is to reduce the surface density of the electrode coating, so that the distance that lithium ions need to migrate during charging is shortened, so that they can reach the inner layer of the negative electrode faster and improve the fast charging capability. However, this method will reduce the capacity of the battery cell and it is difficult to fully demonstrate the high-capacity performance.

[0004] Therefore, how to improve the fast charging capability of cylindrical 21700 high-capacity batteries has become a major challenge facing the industry. Summary of the invention

[0005] The purpose of this application is to provide a cylindrical 21700 high-capacity fast-charging lithium battery and its preparation process, using a high-nickel positive electrode and a silicon-doped graphite negative electrode, and a single-layer coated diaphragm, with the coating facing the negative electrode and the base film facing the positive electrode, to reduce the interface impedance and accelerate the migration of lithium ions. At the same time, combined with the optimized surface density and compaction design, the high-capacity performance of the 21700 battery cell is improved.

[0006] To achieve the above objectives, this application provides the following technical solutions: In the first aspect, the present application proposes a cylindrical 21700 high-capacity fast-charging lithium battery, wherein the lithium battery comprises: a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator; The positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector, wherein the positive electrode slurry includes a high-nickel MCN active material doped with special elements and coated with oxide on the surface, a conductive agent, and polyvinylidene fluoride; The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector, wherein the negative electrode slurry includes a graphite active material doped with a silicon-based material, a conductive agent, sodium carboxymethyl cellulose, and styrene-butadiene rubber; The separator is a single-sided coated separator with polypropylene or polyethylene as the substrate, the substrate surface faces the positive electrode sheet, and the coating surface faces the negative electrode sheet.

[0007] As a specific solution in the technical solution of this application, the positive electrode current collector is an aluminum foil with a thickness of 12-20 μm, and the positive electrode slurry is coated on both sides of the positive electrode current collector with a surface density of 40-48 mg / cm 2 , compacted density is 3.3-3.7g / cm 3 .

[0008] As a specific solution in the technical solution of this application, the positive electrode active material is a high-nickel MCN material doped with special elements and coated with oxides on the surface, with a particle size d50 of 8-12 μm and a specific surface area of ​​0.4-0.6 m 2 / g, the nickel content is 90-95%, and the positive electrode conductive agent is conductive carbon black and multi-walled carbon nanotubes.

[0009] As a specific solution in the technical solution of this application, the negative electrode current collector is a copper foil with a thickness of 6-12 μm, and the negative electrode slurry is coated on both sides of the negative electrode current collector with a surface density of 20-24 mg / cm 2 , compacted density 1.5-1.7g / cm 3 .

[0010] As a specific solution in the technical solution of this application, the negative electrode active material is a mixture of graphite and a silicon-based alloy, the graphite mass accounts for 75%-90%, the silicon-based alloy includes silicon-oxygen material and silicon-carbon material, the particle size d50 of the graphite active material is 10-20 μm, and the specific surface area is 1-2 m2 / g, the particle size d50 of silicon alloy active material is 5-10μm, and the specific surface area is 1-2m 2 / g, and the negative electrode conductive agent is conductive carbon black and single-arm carbon nanotubes.

[0011] As a specific solution in the technical solution of the present application, the coating of the diaphragm is selected from one of alumina, boehmite, a mixture of alumina and nanofibers, and a mixture of boehmite and nanofibers, and the porosity of the diaphragm is 35%-50%.

[0012] As a specific solution in the technical solution of the present application, the electrolyte includes lithium hexafluorophosphate electrolyte, solvent and film-forming additive, and the solvent includes ethylene carbonate with a volume fraction of 5-30%, ethyl methyl carbonate with a volume fraction of 5-30%, and dimethyl carbonate with a volume fraction of 20-60%.

[0013] As a specific solution in the technical solution of the present application, the film-forming additives include but are not limited to: fluoroethylene carbonate, tri(trimethylsilyl) phosphate, (2-fluoromalonate) lithium difluoroborate, trimethyl borate, triethyl borate, tripropyl borate, tri(hexafluoroisopropyl) borate, triphenyl borate, and vinyltrimethylsilane.

[0014] In the second aspect, the present application proposes a preparation process of a cylindrical 21700 high-capacity fast-charging lithium battery, wherein the preparation process comprises the following steps: Step 1: First, N-methylpyrrolidone, polyvinylidene fluoride and multi-arm carbon nanotubes are prepared into a conductive glue with a solid content of 4% to 8%, and then positive electrode active material and conductive carbon black are added and stirred to obtain positive electrode slurry. Then, the positive electrode slurry is coated on aluminum foil, and the positive electrode sheet is made through drying, rolling, slitting and baking; Step 2: first prepare a 1-2% solid content glue solution with deionized water, sodium carboxymethyl cellulose and single-arm carbon nanotubes, add negative electrode active material and conductive carbon black to prepare an initial slurry, then add styrene-butadiene rubber and stir evenly to obtain a negative electrode slurry; coat the negative electrode slurry on copper foil, and prepare a negative electrode sheet after drying, rolling, slitting and baking.

[0015] Step 3: The positive electrode sheet, the negative electrode sheet and the separator are wound to form a dry electrode group, the dry electrode group is assembled to form a battery cell, and the battery cell is subjected to a formation process to obtain a lithium battery.

[0016] As a specific solution in the technical solution of the present application, in the step three, the diaphragm is coated on one side of the polypropylene or polyethylene substrate, and when the dry electrode group is assembled, the substrate surface faces the positive electrode sheet and the coating surface faces the negative electrode sheet.

[0017] Compared with the prior art, the beneficial effects of the present application are: the use of ultra-high nickel positive electrode material and silicon-doped graphite negative electrode, combined with optimized surface density and compaction process, to achieve the high capacity characteristics of the 21700 battery cell. Through the single-sided coating diaphragm design, the coating surface faces the negative electrode to increase the liquid retention on the negative electrode side, reduce the ion migration impedance on the negative electrode side, and support fast charging characteristics; the base film surface faces the positive electrode to reduce liquid absorption, reduce the impedance on the positive electrode side, and increase the lithium ion migration rate. While this solution significantly improves the fast charging capability of the battery cell, it ensures the full utilization of the high capacity characteristics without increasing additional material costs. This design not only improves battery performance, but also ensures cost-effectiveness, achieving dual optimization of economic benefits and technical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the DCR diagram before the cycle proposed in the embodiment of the present application; Figure 2 This is a 0.5C charge and 1C discharge cycle diagram proposed in the embodiment of the present application; Figure 3 This is a fast charging 1C charging and discharging cycle diagram proposed in an embodiment of the present application; Figure 4 This is a diagram showing the effect of impedance on capacity after fast charging cycle proposed in an embodiment of the present application; Figure 5 This is a DCR growth diagram of the fast charging cycle process proposed in the embodiment of the present application. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution in the embodiment of the present invention will be further clearly and completely described below. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] In order to improve the fast charging capability of the cylindrical 21700 high-capacity battery cell proposed in the background technology, this embodiment proposes a cylindrical high-capacity lithium-ion battery that supports fast charging cycles, including a positive electrode sheet, a negative electrode sheet, an electrolyte, a separator, and structural parts for assembling the battery.

[0021] The positive electrode sheet is composed of a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector. The positive electrode slurry includes 94-98% by mass of active material, 1-3% of conductive agent, and 1-3% of polyvinylidene fluoride. The positive electrode active material is a high-nickel NCM material, specifically a high-nickel NCM material doped with special elements and coated with surface oxides, with a particle size d50 of 8-12 μm and a specific surface area of ​​0.4-0.6 m 2 / g, the nickel content is 90-95%, mainly because other elements such as magnesium (Mg), aluminum (Al), chromium (Cr), etc. are doped into the crystal structure of the high-nickel NCM material, and a layer of oxides such as aluminum oxide (Al2O3), titanium oxide (TiO2), zirconium oxide (ZrO2), etc. are coated on the surface of the high-nickel NCM material. The positive electrode conductor includes conductive carbon black SP and multi-walled carbon nanotubes CNT. The positive electrode collector is an aluminum foil with a thickness of 12-20μm, and the positive electrode slurry is coated on both sides of the positive electrode collector with a surface density of 40-48mg / cm 2 ; compacted density is 3.3-3.7g / cm 3 .

[0022] The negative electrode sheet is composed of a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector. The negative electrode slurry includes 88-95% by mass of active material, 1-3% of conductive agent, 1-3% of sodium carboxymethyl cellulose CMC, and 1-3% of styrene-butadiene rubber SBR. The negative electrode active material is a mixture of artificial graphite and silicon alloy, in which the mass proportion of graphite in the mixture is 75%-90%. The silicon system includes silicon-oxygen material and silicon-carbon material. The particle size d50 of the negative electrode graphite active material is 10-20 μm, and the specific surface area is 1-2 m 2 / g, the particle size d50 of negative electrode silicon active material is 5-10μm, and the specific surface area is 1-2m 2 / g. The negative electrode conductive agent is conductive carbon black SP and single-arm carbon nanotube SWCNT. The negative electrode current collector is a copper foil with a thickness of 6-12μm; the negative electrode slurry is coated on both sides of the negative electrode current collector with a surface density of 20-24mg / cm 2 , compacted density 1.5-1.7g / cm 3 .

[0023] The electrolyte includes an electrolyte LiPF6 with a concentration of 0.6-1.5 mol / L, an organic solvent and a film-forming additive. The organic solvent is a mixed organic solvent of ethylene carbonate EC, 5-30% ethyl methyl carbonate EMC, and 20-60% dimethyl carbonate DMC, accounting for 5-30% of the solvent volume fraction. The film-forming additive includes but is not limited to fluoroethylene carbonate, tri(trimethylsilyl) phosphate, (2-fluoromalonate) lithium difluoroborate, trimethyl borate, triethyl borate, tripropyl borate, tri(hexafluoroisopropyl) borate, triphenyl borate, and vinyltrimethylsilane.

[0024] The battery separator is a single-sided coated separator with polypropylene PP or polyethylene PE as the base, the coating is alumina or boehmite or a mixture of them and nanofibers, and the porosity of the separator is 35%-50%. The base surface of the separator faces the positive electrode sheet, and the coating surface faces the negative electrode sheet. The battery cycle charge and discharge standard is: 25℃ +1C / -1C, 4.2-2.75V, 0.01C cutoff.

[0025] As a specific embodiment of the present application, the preparation method of the lithium ion battery comprises the following steps: step 1, firstly, N-methylpyrrolidone NMP, polyvinylidene fluoride PVDF and multi-arm carbon nanotubes CNT are prepared into a conductive glue with a solid content of 4% to 8%, and then the positive electrode active material and conductive carbon black SP are added and stirred to obtain a positive electrode slurry, and then the positive electrode slurry is coated on an aluminum foil, and then dried, rolled, cut and baked to form a positive electrode sheet; step 2, first deionized water, a negative electrode binder sodium carboxymethyl cellulose CM C. Single-arm carbon nanotubes SWCNT are made into a 1-2% solid content glue, and negative electrode active materials and conductive carbon black SP are added to make an initial slurry, and then a binder styrene-butadiene rubber SBR is added and stirred evenly to obtain a negative electrode slurry; the negative electrode slurry is coated on copper foil, and after drying, rolling, slitting, and baking, a negative electrode sheet is made; step three, the positive electrode sheet, the negative electrode sheet, and the diaphragm are wound into a dry electrode group, and the dry electrode group is assembled into a battery cell, and the battery cell is subjected to a formation process to obtain the 21700 lithium-ion battery with high capacity and fast charging cycle. It should be noted that structural parts are used in the process of winding the positive electrode sheet, the negative electrode sheet, and the diaphragm into a dry electrode group, and the dry electrode group is assembled into a battery cell. The structural parts include but are not limited to the battery cell top cover, steel / aluminum shell, positive and negative electrode soft connection, battery soft connection bar, explosion-proof plate, bus bar and soft connection, protective plate, outer packaging, and output connector. In addition, in step three, the diaphragm is coated on one side of the polypropylene or polyethylene substrate. During the assembly of the dry electrode group, the substrate surface faces the positive electrode sheet, and the coating surface faces the negative electrode sheet. This is mainly because the high liquid absorption performance of the coating surface is used to provide more liquid retention for the negative electrode side to avoid insufficient electrolyte inside the negative electrode during fast charging to assist lithium ions to embed into the negative electrode layer, thereby reducing the ion migration impedance on the negative electrode side to support the fast charging characteristics; at the same time, the base film faces the positive electrode, because the electrolyte formula matching the high nickel positive electrode must add a positive electrode film-forming protective agent to reduce the interface side reaction on the positive electrode side. The positive electrode interface film-forming protective agent will increase the interface ion migration impedance on the positive electrode side, which is not conducive to the release of lithium ions during fast charging. The base film surface of the diaphragm faces the positive electrode, which will reduce the liquid absorption of the positive electrode sheet and reduce the impedance on the positive electrode side. Therefore, using a single-layer coated diaphragm, the coating layer faces the negative electrode, and the base film faces the positive electrode, which can greatly reduce the impedance of the positive and negative electrode interfaces, increase the lithium ion migration rate, and thus greatly improve the fast charging capability.

[0026] Example 1 This embodiment provides a cylindrical 21700 type high capacity and fast charging capable lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, a separator and a structural member. The battery manufacturing and cycle system are shown in the above technical solution.

[0027] Comparative Example The difference from Example 1 is that the separator coating surface used in the comparative battery faces the positive electrode, and the base surface faces the negative electrode.

[0028] The performance of the lithium battery prepared in this example was tested with reference to the comparative example.

[0029] like Figure 1 It is a test diagram of the charge level of fresh, uncycled batteries at different charging states at 25° C. The DC internal resistance DCR of the battery cells of Example 1 at different battery states of charge SOC is slightly lower than that of the comparative example.

[0030] like Figure 2-3 As shown, under the normal rate 0.5C charging / standard rate 1C discharging system, after 1000 cycles, the cycle retention rates of Example 1 and the comparative example are basically close, and Example 1 is only slightly better than the comparative example; while under the cycle system of high rate 1C charging / standard rate 1C discharging, the cycle life of Example 1 exceeds 600 times 80%, while that of the comparative example is only about 200 times 80%. This is mainly because in the cycle process of conventional charging rate, it is less difficult for lithium ions to enter the negative electrode and is less affected by impedance. Therefore, under this relatively loose system, Example 1 and the comparative example do not show obvious differences; and under the cycle system of extremely high negative rate charging, the main test is the difficulty of lithium ions quickly embedding into the negative electrode, and the key factor affecting the rapid migration of lithium ions is impedance. Figure 4 It can be seen that through the depolarization capacity loss analysis, Example 1 loses a total of 450mAh capacity in the cycle, the loss affected by impedance accounts for 120mAh, and the remaining active lithium and active material losses account for 330mAh; the comparative example loses a total of 1000mAh in the cycle, the loss affected by impedance is 650mAh, and the remaining active lithium and active material losses account for 350mAh. It can be seen that under the fast charge cycle format, the difference in capacity loss values ​​between Example 1 and the comparative example is 550mAh, which is close to the difference in capacity loss affected by impedance of 530mAh, that is, the difference in fast charge cycle capacity retention rate between the two is almost entirely caused by the difference in impedance. In the fast charge cycle process, with the gradual consumption of the electrolyte at the interface between the positive and negative electrodes, the electrolyte inside the negative electrode sheet continues to decrease, and the ion migration impedance increases, making it difficult for lithium ions to be embedded in the inner layer of the negative electrode; at the same time, the electrolyte of the high nickel system needs to protect the positive electrode film to stabilize the structure, and the positive electrode interface impedance will be slightly larger, so the impedance is easy to increase under the fast charge format and affect the cycle. In Example 1, the coating surface faces the negative electrode. The coating surface can absorb more electrolyte due to its larger specific surface area, so that the distribution of the electrolyte in the positive and negative electrode sheets can be adjusted, so that the negative electrode sheet can absorb the electrolyte adsorbed by the coating surface, while the positive electrode sheet absorbs less electrolyte. As a result, the interface impedance of the positive and negative electrodes is lower than that of the control example, thereby maintaining a better cycle result.

[0031] like Figure 5 As shown in the figure, the growth of DCR during the cycle of the two cases shows that the growth rate of DCR in Example 1 is significantly lower than that in the comparative example, which is consistent with the conclusion of the above analysis.

[0032] Therefore, the present application provides a method for improving the fast charging performance of cylindrical 21700 high-capacity battery cells. This method can significantly improve the fast charging capability of the battery cells without increasing costs or reducing battery cell safety, while ensuring that the high capacity is not affected.

[0033] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A cylindrical 21700 high-capacity fast-charge lithium battery, characterized in that: The lithium battery comprises: a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator; The positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector, wherein the positive electrode slurry includes a high-nickel MCN active material doped with special elements and coated with oxide on the surface, a conductive agent, and polyvinylidene fluoride; The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector, wherein the negative electrode slurry includes a graphite active material doped with a silicon-based material, a conductive agent, sodium carboxymethyl cellulose, and styrene-butadiene rubber; The separator is a single-sided coated separator with polypropylene or polyethylene as the substrate, the substrate surface faces the positive electrode sheet, and the coating surface faces the negative electrode sheet.

2. The lithium battery according to claim 1, characterized in that The positive electrode current collector is an aluminum foil with a thickness of 12-20 μm, and the positive electrode slurry is coated on both sides of the positive electrode current collector with a surface density of 40-48 mg / cm 2 , compacted density is 3.3-3.7g / cm 3 .

3. The lithium battery according to claim 1, characterized in that The positive electrode active material is a high-nickel MCN material doped with special elements and coated with oxides on the surface, with a particle size d50 of 8-12 μm and a specific surface area of ​​0.4-0.6 m 2 / g, the nickel content is 90-95%, and the positive electrode conductive agent is conductive carbon black and multi-walled carbon nanotubes.

4. The lithium battery according to claim 1, characterized in that The negative electrode current collector is a copper foil with a thickness of 6-12 μm, and the negative electrode slurry is coated on both sides of the negative electrode current collector with a surface density of 20-24 mg / cm 2 , compacted density 1.5-1.7g / cm 3 .

5. The lithium battery according to claim 1, characterized in that: The negative electrode active material is a mixture of graphite and silicon alloy, wherein the graphite accounts for 75%-90% by weight, and the silicon alloy includes silicon-oxygen material and silicon-carbon material. The particle size d50 of the graphite active material is 10-20 μm, and the specific surface area is 1-2 m 2 / g, the particle size d50 of silicon alloy active material is 5-10μm, and the specific surface area is 1-2m 2 / g, and the negative electrode conductive agent is conductive carbon black and single-arm carbon nanotubes.

6. The lithium battery according to claim 1, characterized in that: The coating of the diaphragm is selected from one of alumina, boehmite, a mixture of alumina and nanofibers, and a mixture of boehmite and nanofibers. The porosity of the diaphragm is 35%-50%.

7. The lithium battery according to claim 1, characterized in that: The electrolyte comprises lithium hexafluorophosphate electrolyte, solvent and film-forming additive, wherein the solvent comprises ethylene carbonate with a volume fraction of 5-30%, ethyl methyl carbonate with a volume fraction of 5-30%, and dimethyl carbonate with a volume fraction of 20-60%.

8. The lithium battery according to claim 7, characterized in that: The film-forming additives include, but are not limited to, fluoroethylene carbonate, tri(trimethylsilyl) phosphate, lithium (2-fluoromalonate)difluoroborate, trimethyl borate, triethyl borate, tripropyl borate, tri(hexafluoroisopropyl) borate, triphenyl borate, and vinyltrimethylsilane.

9. A process for preparing a lithium battery according to any one of claims 1 to 8, characterized in that: The preparation process comprises the following steps: Step 1: First, N-methylpyrrolidone, polyvinylidene fluoride and multi-arm carbon nanotubes are prepared into a conductive glue with a solid content of 4% to 8%, and then positive electrode active material and conductive carbon black are added and stirred to obtain positive electrode slurry. Then, the positive electrode slurry is coated on aluminum foil, and the positive electrode sheet is made through drying, rolling, slitting and baking; Step 2: firstly prepare a 1-2% solid content glue solution with deionized water, sodium carboxymethyl cellulose and single-arm carbon nanotubes, add negative electrode active material and conductive carbon black to prepare an initial slurry, then add styrene-butadiene rubber and stir evenly to obtain a negative electrode slurry; coat the negative electrode slurry on copper foil, and prepare a negative electrode sheet after drying, rolling, slitting and baking; Step 3: The positive electrode sheet, the negative electrode sheet and the separator are wound to form a dry electrode group, the dry electrode group is assembled to form a battery cell, and the battery cell is subjected to a formation process to obtain a lithium battery.

10. The preparation process according to claim 9, characterized in that: In the step three, the diaphragm is coated on one side of the polypropylene or polyethylene substrate, and when the dry electrode group is assembled, the substrate surface faces the positive electrode sheet and the coating surface faces the negative electrode sheet.

Citation Information

Cited By

  • Battery and electric equipment

    CN122576331A

  • Battery cell, battery device, and energy storage device

    WO2026200063A1